Design and Testing of a Small-Scale Composting Facility for Sheep Manure Utilizing Aeration and Thermal Treatment - Jian Wang; Kailin Ren; Longfei Zhang (Agriculture)
Inner Mongolia has the largest sheep population among China’s provinces, resulting in the production of a substantial amount of sheep manure. If left untreated, this manure can contribute to environmental pollution. However, sheep manure serves a dual purpose: it can be both a pollutant and a valuable source of organic fertilizer. Consequently, there is an urgent need to address the environmental issues arising from manure accumulation and its unused status. In this paper, a viable solution is proposed: the conversion of manure into fertilizer through a composting unit incorporating high-temperature aerobic fermentation technology. This unit, tailored for small farms and individual farmers, integrates critical functions such as ventilation, heating, and turning. Additionally, it boasts excellent thermal insulation, enhancing composting efficiency and enabling precise control over fermentation conditions. This design mitigates heat loss and accelerates maturation, addressing common challenges in traditional composting. The design process encompassed both equipment construction and control systems, with a primary focus on compost fermentation and aeration heating. The components were carefully designed or selected based on theoretical analysis and subsequently validated using simulation software, including EDEM and Fluent. The control system seamlessly integrates a touch screen interface, PLC programming, and control circuits to manage air pumps and electric heaters in response to changes in temperature and oxygen concentration. Furthermore, it controls the motors during the recovery phase. A comprehensive performance evaluation was conducted, revealing notable improvements. Under artificially heated conditions, the maximum temperature of the compost increased by approximately 20 °C, the composting cycle was reduced by roughly 4 days, and the seed germination index (GI) rose by about 9% when compared to natural fermentation. Thus, this device significantly accelerates composting and improves fertilizer quality by increasing the decomposition rate.